1984
DOI: 10.1172/jci111422
|View full text |Cite
|
Sign up to set email alerts
|

Suppression by diets rich in fish oil of very low density lipoprotein production in man.

Abstract: A X bstract. The highly polyunsaturated fatty acids in fish oils lower the plasma triglyceride concentration. We have studied the effect of a diet rich in fish oil on the rate of production of the triglyceride-transporting very low density lipoprotein (VLDL). Seven subjects, five normal and two with hypertriglyceridemia received up to 30% of daily energy needs from a fish oil preparation that was rich in eicosapentaenoic acid and docosahexaenoic acid, w-3 fatty acids with five and six double bonds, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
176
7
8

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 581 publications
(209 citation statements)
references
References 31 publications
18
176
7
8
Order By: Relevance
“…This was observed without any change in BMI, lean body mass or diet. The results are similar to those observed by Nestel et al, 1984 who found a 73% decrease in pool size and a 55% decrease in production rate using a considerably higher dose of ®sh oil (up to 30% of daily energy needs). Hepatic and lipoprotein lipase activities did not change after n-3 PUFA supplementation, consistent with other studies (Desager et al, 1989;Bagdade et al, 1990).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This was observed without any change in BMI, lean body mass or diet. The results are similar to those observed by Nestel et al, 1984 who found a 73% decrease in pool size and a 55% decrease in production rate using a considerably higher dose of ®sh oil (up to 30% of daily energy needs). Hepatic and lipoprotein lipase activities did not change after n-3 PUFA supplementation, consistent with other studies (Desager et al, 1989;Bagdade et al, 1990).…”
Section: Discussionsupporting
confidence: 90%
“…A reduction in VLDL-C (750%) and plasma apoB100 was also observed in accordance with the literature (Nestel et al, 1984;Harris, 1989;Berg-Schmidt et al, 1993;Mori et al, 1994). The reduction of VLDL apoB100 means a diminished number of circulating VLDL particles, given that each lipoprotein particle contains only one apoB100 molecule.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Although the physiological basis of metabolic dyslipidaemia appears to be hepatic overproduction of apo-B-containing VLDL particles [46,47], emerging evidence suggests that intestinal overproduction of apo-B-48-containing lipoproteins in insulin-resistant states may be an important contributor to the elevation of circulating triglyceride-rich lipoproteins [17,18,48]. The present study demonstrated that intestinal cells, like hepatocytes [49,50], responded to n-3 FA and decreased the output of triglyceride-rich lipoproteins by lowering the synthesis of apo B-48 and by inhibiting the new formation of lipids. The suppression of apo B-48 was not due to changes in apo B transcription, since Apob 48 mRNA levels were unaffected.…”
Section: Discussionmentioning
confidence: 48%